1999
DOI: 10.1002/(sici)1097-0231(19990228)13:4<242::aid-rcm447>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural elucidation studies of erythromycins by electrospray tandem mass spectrometry

Abstract: Erythromycin A (EryA) was studied by electrospray ionisation tandem mass spectrometry (ESI-MS/MS) with the aim of developing a methodology for the structural elucidation of novel erythromycins developed by biological synthetic methods. Skimmer dissociation along with sequential mass spectrometry studies (up to MS5) have been employed in this study. In the low-resolution MS/MS analysis of the polyketides, there are several fragment ions that are easily assigned to various neutral losses. These have all been con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
28
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 0 publications
4
28
0
1
Order By: Relevance
“…Protonated SP1 (with a C-9 hydroxyl instead of a carbonyl) and SP4 (in which the C-9 oxygen is involved in binding to the trimethylbenzyl protecting group) exhibit virtually no water loss in either the CAD or IRMPD spectra, corroborating the C-6/C-9 oxonium formation mechanism proposed by Gates et al [4], in which the carbonyl oxygen at C-9 was involved in dehydration. The dissociation spectrum of protonated SP3 displays a small signal corresponding to water loss; the presence of a new hydroxyl group at C-3 likely accounts for this fragmentation pathway.…”
Section: Protonated Macrolides and Analogssupporting
confidence: 73%
See 3 more Smart Citations
“…Protonated SP1 (with a C-9 hydroxyl instead of a carbonyl) and SP4 (in which the C-9 oxygen is involved in binding to the trimethylbenzyl protecting group) exhibit virtually no water loss in either the CAD or IRMPD spectra, corroborating the C-6/C-9 oxonium formation mechanism proposed by Gates et al [4], in which the carbonyl oxygen at C-9 was involved in dehydration. The dissociation spectrum of protonated SP3 displays a small signal corresponding to water loss; the presence of a new hydroxyl group at C-3 likely accounts for this fragmentation pathway.…”
Section: Protonated Macrolides and Analogssupporting
confidence: 73%
“…Based on the 18 O-labeling, it was found that the first loss of water occured from the C-9 carbonyl group, indicating that the carbonyl oxygen was protonated, not the more basic amine group in the desosamine moiety. They also confirmed via MS n experiments that the first macrolide ring cleavage involved the C-13 position and adjacent oxygen, with the net loss identified as a substituted ketone moiety [4]. Volmer and Hui incubated erythromycin in aqueous solutions at non-physiological pH [6], and subsequently used solid phase microextraction/high performance liquid chromatography/ESI-MS to determine the decomposition products of protonated erythromycin in a triple quadrupole mass spectrometer.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…We therefore also performed fragmentation analysis on acetate starter EB (Ac-EB) (Structure 3), to investigate whether fragments containing the starter acid could be pinpointed on the fragmentation pathway. Previous MS-MS studies [11,12] had achieved this using erythromycin A analogs with different starter acids incorporated.…”
mentioning
confidence: 99%